Bioinformatics analysis combined with experimental validation reveals the biological role of the ILK gene in prostate cancer - Xiao-xiang Yu; Yi Liu; Rong-jiang Luo; Zi-xuan Song; Wen-kai Chen; Zeng-mi Mo; Feng-jing Wang (Discover Oncology)
Abstract Background Prostate cancer (PCa) is a prevalent urological malignancy. The integrin-linked kinase (ILK) gene has been identified as an oncogenic driver in hormonal cancers, including PCa. Methods To identify key genes in PCa, we utilized differential gene expression analysis and Weighted Gene Co-expression Network Analysis (WGCNA). The ILK gene was silenced using short interfering RNA (siRNA), and subsequent experiments focusing on cellular functionality were conducted to evaluate its impact on cell proliferation, apoptosis, and cell cycle. We examined the expression of autophagy-related and cell cycle-related proteins, including MAP1LC3A, BECN1, C-MYC, TP53, and MDM2. Moreover, we conducted Mfuzz expression pattern clustering analysis, gene set enrichment analysis (GSEA), immune function analysis, transcription factor (TF) analysis, and drug prediction. Results 544 significant genes were identified by WGCNA. The protein–protein interaction (PPI) network analysis revealed that MYC was the central regulatory gene, with the intersected genes mainly involved in regulating cell adhesion and drug metabolism in prostate cancer (PCa). Experimental results showed LNCaP cell proliferation was significantly inhibited in the knockdown groups (P < 0.001). Moreover, ILK silencing increased apoptosis in LNCaP cells compared to normal cells and empty vectors, and transfected LNCaP cells were arrested in the S phase of the cell cycle. Notably, C-MYC expression decreased following ILK silencing. Subsequently, we further identified ILK-related regulatory biomarkers. Conclusions The ILK is an oncogene mainly through influencing the C-MYC in PCa. Inhibition of ILK expression would be a promising method for treating the development and progression of PCa.